Mechanism of biodegradation of paraquat by Lipomyces starkeyi. - Carr, R J (1985)
The biodegradation of ring-14C- and methyl-14C-labeled paraquat by the soil yeast Lipomyces starkeyi was studied in vitro. It was found that the degradation of paraquat (acting as a sole source of culture nitrogen) resulted in the accumulation in the extracellular medium of radiolabeled acetic acid. The culture also evolved radiolabeled CO2. The results suggest that the degradation of paraquat by L. starkeyi is associated with the integrity of the cell wall and that disruption or removal of the wall results in a complete loss of degradative capability. A mechanism for the degradation of paraquat by this organism is postulated.